FAKTOR-FAKTOR YANG MEMENGARUHI KADAR MERKURI (Hg) PADA AIR SUMUR PENDUDUK DI DESA TAMIANG KECAMATAN KOTANOPAN KABUPATEN MANDAILINGNATAL - Siregar, Nurul Rahmah; Pandia, Setiaty; Ashar, Taufik (Universitas Aufa Royhan, 2016)
Ground water could be contaminated by heavy metal Mercury (Hg), which could come from the activity of gold mining at the side of river flow. Waste with mercury content will flow to the river so could pollute wellwater along the watershed. The contamination of wellwater is affected by some factors.The objective of the research was to analyze some factors which influenced mercury (Hg) content in people’s wellwater at Tamiang Village, Kotanopan Subdistrict, Mandailing Natal District. The research used an analytic survey with cross sectional study. The samples of the research were the wellwater used as drinking water and the soil around these sites. The data were analyzed by using Mann-Whitney test and multiple linear regression tests.The result of the research showed that the highest mercury measured was 0,00207mg/l, Variables of the distance of polluting source from the wells (p = 0.000), and soil porosity (p = 0.000) influenced the mercury (Hg) content in wellwater, while the age of the wells (p = 0.183), well construction/physic (p >0.25), wellwater temperature (p = 0.760), and well depth (p = 0.594)did not have any influence on the mercury (Hg) content in wellwater. The multiple linear regression tests showed that the mercury content in wellwater was affected by the variable of the distance of the polluting source from the wells with coefficient value Exp (β) of 5.882E6 and the soil porosity with coefficient value Exp (β) of 5.317E-5.